Modelling of the distribution of coal tar product qualities from a tar distillation plant - Mokoena, Lehlohonolo Christopher (University of the Witwatersrand, Johannesburg, 2024)
This work presents the simulation modelling and optimisation of a coal tar distillation process to improve the product qualities and increase overall product revenue. The coal tar distillation process consists of three vacuum distillation units and a flash column. The system produces four distillate products: light oil, refined chemical oil (RCO), light creosote, and heavy oil, as well as the residue pitch used as a binder in the manufacturing of electrodes in the aluminium industry. The simulation model was developed in HYSYS using the actual plant mass balance and operating conditions for the production of a residue pitch product with a softening point of 115 – 118 Metller and associated distillates as reference. A mass balance reconciliation technique using an optimiser in HYSYS was applied to fit the plant quality and distillate rate data through adjustment of the Murphee tray efficiencies for each column. The simulation model was validated by simulating the manufacturing of a softer pitch product of softening point 68 – 73 Ring and ball using conditions specified for this particular product and its related distillate products. Through this process, the base conditions were established for the hard and soft pitch production processes. The resultant pitch yield of softening point 115 – 118 M was 42 %, with the light creosote distillate yield at 27 %, as for the softer pitch, the initial yield was estimated at 65 %, and the light creosote at 9,6 %. Following the model development and the establishment of base conditions, a sensitivity analysis focusing on product quality distribution was done to develop an operating philosophy of the process followed by an optimisation process carried out using HYSYS original optimiser to maximise the objective function defined as the sum of product revenue sales with constraints placed on product qualities and adjustable parameters selected as column reflux and boil up ratio as well as the top and bottom temperatures. From the optimisation results, the general adjustment on the first two columns was the drop-down of column top and bottom temperatures by increasing the reflux ratio and reducing the boil-up rate. The light oil product quality in the simulation of a 115 – 118 M pitch improved by decreasing the naphthalene content from 48 % to less than 8,0 % as required by standard operation, with the naphthalene recovery in the RCO stream increasing from 44 % to 67 %. The optimisation process had a large impact on the product yields, where the pitch product 115 – 118 M showed an increase in yield from 42 % to 49 %, which is close to the general yield of 50% mentioned in the literature and normally expected from a coal tar distillation process. and the light creosote distillate product had a positive yield increase of 14 % from the initial value. The overall revenue benefit for the production of a hard pitch improved by an estimated figure of 3,1 % per annum from the initial value (non-optimised condition). In the production of a softer pitch product, the total revenue benefit was 3,2 % higher per annum in comparison to the non-optimised condition.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; coal tar product; tar distillation plant; SDG-8: Decent work and economic growth; SDG-7: Affordable and clean energy